Pupillary Responses During a Dual Task: Effect of Noise Attenuation on the Timing of Cognitive Resource Allocation. - Bianchi, Federica; Jonsson, Sindri; Christiansen, Torben; Ng, Elaine Hoi Ning (Trends in Hearing, 2025)
Although multitasking is a common everyday activity, it is often challenging. The aim of this study was to evaluate the effect of noise attenuation during an audio-visual dual task and investigate cognitive resource allocation over time via pupillometry. Twenty-six normal hearing participants performed a dual task consisting of a primary speech recognition task and a secondary visual reaction-time task, as well as a visual-only task. Four conditions were tested in the dual task: two speech levels (60- and 64-dB SPL) and two noise conditions (No Attenuation with noise at 70 dB SPL ; Attenuation condition with noise attenuated by passive damping). Elevated pupillary responses for the N o Attenuation condition relative to the A ttenuation and visual-only conditions indicated that participants allocated additional resources on the primary task during the playback of the first part of the sentence, while reaction time to the secondary task increased significantly relative to the visual-only task. In the A ttenuation condition, participants performed the secondary task with a similar reaction time relative to the visual-only task (no dual-task cost), while pupillary responses revealed allocation of resources on the primary task after completion of the secondary task. These findings reveal that the temporal dynamics of cognitive resource allocation between primary and secondary task were affected by the level of background noise in the primary task. This study demonstrates that noise attenuation, as offered for example by audio devices, frees up cognitive resources in noisy listening environments and may be beneficial to improve performance and decrease dual-task costs during multitasking.